1998
DOI: 10.2176/nmc.38.657
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Mycotic Aneurysm Treated with Endovascular Occlusion —Case Report—

Abstract: A 56-year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Most of these aneurysms are distal and involve the middle cerebral artery 1,2 . The overall mortality rate among these patients is 60%, and increases to 80% in cases associated with subarachnoid hemorrhage (SAh) 2,4,5 . IIAs can be treated with antibiotic therapy alone, with an unpredictable evolution: they can regress, enlarge, stabilize or even rupture 6 .…”
Section: Dr Eduardo Wajnberg -Rua Lopes Quintas 100 / 602 -22460-010mentioning
confidence: 99%
“…Most of these aneurysms are distal and involve the middle cerebral artery 1,2 . The overall mortality rate among these patients is 60%, and increases to 80% in cases associated with subarachnoid hemorrhage (SAh) 2,4,5 . IIAs can be treated with antibiotic therapy alone, with an unpredictable evolution: they can regress, enlarge, stabilize or even rupture 6 .…”
Section: Dr Eduardo Wajnberg -Rua Lopes Quintas 100 / 602 -22460-010mentioning
confidence: 99%
“…Review of the 15 reported cases of aneurysms located at the cortical segment of the MCA showed that 14 cases resulted from infection and one occurred secondary to arterial dissection. 1,2,[5][6][7][9][10][11][12][15][16][17]19,20) Several surgical strategies for the treatment of distal MCA aneurysms have been reported. The first choice of the treatment for cerebral aneurysms is neck clipping, but this procedure is performed only for aneurysms located at the M 2 or M 3 segment of the MCA.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatments have been advocated 13,32) for treating infectious aneurysm, but the principal goals should be to eliminate the aneurysm from the circulation and to preserve flow to the distal vasculature. However, infectious aneurysms may incorporate the parent and distal vessels, especially in the distal MCA as well as in other locations, and are often difficult to obliterate without compromising cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%